PERAN GURU SEBAGAI AGEN PERUBAHAN DALAM MEMBANGUN KESADARAN SOSIAL DAN LINGKUNGAN PESERTA DIDIK DI SEKOLAH DASAR - Erna; Nadia Mustopa; M.Taufik Hidayat; Syakira Eka Windari; Riesti Yulvianti; Monalisa; Dine Trio Ratnasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe the role of the teacher as an agent of change in building social and environmental awareness among students in elementary schools. The study uses a descriptive qualitative approach. The research location is SDN 3 Guradog, Lebak Regency, Banten. The research was conducted for approximately two months, including one month for data collection and one month for data processing. The population and sample of this study are the class teacher and fourth-grade students of SDN 3 Guradog. Data collection techniques included observation, which was conducted to directly observe the teacher's role as an agent of change in building social and environmental awareness among students , and interviews, which were conducted to determine the teacher's role in applying and building social awareness through the implementation of Social Studies (IPS) learning. The discussion results indicate that teachers have a very important role as agents of social change in society. The teacher is a central figure in the world of education, having a significant influence in transferring knowledge, values, and relevant skills. School is a place to build students' social awareness of the surrounding environment , and social awareness is the ability to read and understand the social circumstances around them. The conclusion of this observation is to find out the changes that exist within the scope of the teacher in conducting IPS learning, with the teacher acting as an agent of change. Keyword: Teacher; Agent of Change; Social Awareness; Environment; Elementary School. (;))